The Safety and Adherence To Prophylactic Anticoagulation During Induction Chemotherapy In Adults With Acute Lymphoblastic Leukemia - Grace, Rachael F.; Stevenson, Kristen E.; Neuberg, Donna S.; Sallan, Stephen E.; Silverman, Lewis B.; DeAngelo, Daniel J.; Connors, Jean M. (Blood, 2013)
Treatment for acute lymphoblastic leukemia (ALL) in adults confers a high risk of venous thromboembolic (VTE) complications with a 34% VTE rate reported in our previous study. We describe the safety and adherence to prophylactic anticoagulation during induction in adults treated on the Dana-Farber Cancer Institute (DFCI) ALL consortium protocol. 110 patients (pts) with ALL ages 18-50 years enrolled on a high-risk pediatric treatment regimen through the DFCI ALL Consortium from September 2010 through June 2013. All pts received a multi-agent remission induction regimen including asparaginase (ASP). After initial accrual, a high rate of ASP related toxicity events including VTE led to a protocol amendment with recommended guidelines for prophylactic anticoagulation with enoxaparin, dalteparin, fondaparinux, or unfractionated heparin during induction therapy. Induction therapy was modified so that the first 66 pts received 2500 IU/m2 of PEG-ASP, and the final 44 pts received 25,000 IU/m2 of native E.coli ASP. Data were collected prospectively regarding the use, monitoring, and side effects of prophylactic anticoagulation. Eligible pts included those with Philadelphia-negative ALL who received the induction dose of ASP and were either enrolled pre-amendment (n=47) or participated in prophylactic monitoring post-amendment (n=21). 21 of 27 (78%) pts enrolled post-amendment received prophylactic anticoagulation during induction. Low molecular weight heparin (dalteparin, n=13 and enoxaparin, n=8) was given once daily in 90% and twice daily in 10% of the pts receiving prophylaxis. 0% (0/21) of pts receiving prophylactic anticoagulation had a VTE during induction; 11% (5/47) without prophylactic anticoagulation prior to the amendment had a VTE (p=0.31). No pts on prophylactic anticoagulation had grade ≥2 bleeding. Of the pts who received prophylactic anticoagulation, the following bleeding complications occurred during induction: excess bruising (n=4), drainage from line site (n=2), grade I rectal bleeding (n=1). While on anticoagulation, platelet (plt) transfusion criteria varied; the majority were transfused to plts ≥ 30 kcells/ul. Anticoagulation was held for procedures (86%), thrombocytopenia< 30 kells/ul (33%), and bleeding (5%). Antithrombin levels were followed in 10 of the 21 subjects with a median nadir on week 2 of induction (median 68%, range 47-124%). Fibrinogen levels also had a median nadir on week 2 of 150 mg/dl (range 97-458 mg/dl). Cryoprecipitate was infused in 2 pts receiving anticoagulation. Prophylactic anticoagulation can be administered during multi-agent remission induction to adults with ALL. In this study, there was no increase in number or severity of bleeding events on prophylactic anticoagulation. Continued follow up of these pts on prophylaxis during consolidation chemotherapy will allow for additional safety information. Off Label Use: Low molecular weight heparin for prophylactic anticoagulation during acute lymphoblastic leukemia therapy. Silverman:EUSA: Membership on an entity's Board of Directors or advisory committees; Jazz: Membership on an entity's Board of Directors or advisory committees; Sigma Tau: Membership on an entity's Board of Directors or advisory committees. TableThe Incidence of Thrombotic and Bleeding Events Based on Common Toxicity Criteria and Event Reports in Adult ALL patients during Induction Categorized by Asparaginase (ASP) type and with and without Prophylactic AnticoagulationNo Anticoagulation Prophylaxis IV PEG ASP 2500 IU/m2 N (%)Anticoagulation Prophylaxis IM E. coli ASP 2000 IU/m2 N (%)Total Patients4721Thrombotic Events5 (11)0 (0)Bleeding Events17 (36)6 (29)